Assessment of Various Parameters of Dental Anxiety Among Nursing Students in Rural and Urban Area of Bareilly City India –A Cross Sectional Survey - Yadav, Karnika; Lakshminaryan, N. (Nepal Medical College Journal, 2019)
To assess the various parameters of dental anxiety among nursing students in rural and urban area of Bareilly city India. A cross-sectional survey was conducted among nursing students aged 18 to 25 years in Bareilly city of Uttar Pradesh State in India. Dental anxiety was measured using Modified Dental Anxiety Scale (MDAS). It consists of three six-item scales that also use the Likert format. The data obtained were analysed using Analysis of variance (ANOVA). The study group individuals in majority were slightly anxious (59.4% and 47.5%) when questioned about their feelings on visit to dentist and sitting in dentist’s waiting area, while they would feel extremely anxious (29.9%) if they were to receive local anesthesia respectively. The conclusion drawn from the present study was that all are "slightly anxious" as compare to others.